The provisions of the temples in Islamic jurisprudence (Journal of the College of Basic Education, 2022)
Temples have a special ruling in Islamic law, especially since they carry ideas and beliefs on a framework and content other than the frameworks and contents that came with Islamic law, and research in this field gives a special character based on how Islamic law deals with these temples through the limits and controls that it set towards them . As for the research plan: I divided it into five topics.